2015
DOI: 10.1371/journal.pone.0142092
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Ingredients Contained in Over the Counter (OTC) Cough Syrup Formulations in Kenya. Are They Harmful to Infants?

Abstract: BackgroundCough syrups are widely used in the developing world, but safety of their use in infants and children less than two years has not been well documented. Some syrups contain multiple combinations of such drugs as promethazine, diphenhydramine and ephedrine; which are individually now contraindicated in children less than two years. Despite this, the syrups are available as over the counter drugs and may be dispensed to mothers who are unaware of the potentially hazardous effects to their infants. A des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
0
5
0
1
Order By: Relevance
“…This is despite the low cost of cough medicines and continuing aggressive marketing by manufacturers in Kenya, which has been identified as one of the reasons why cough medicines are prescribed. It has also been suggested that health workers have a poor understanding of the ingredients in cough medicines . This suggests that marketing or some perceived benefit of active ingredients where they are known might influence changes in the pattern of active ingredients over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is despite the low cost of cough medicines and continuing aggressive marketing by manufacturers in Kenya, which has been identified as one of the reasons why cough medicines are prescribed. It has also been suggested that health workers have a poor understanding of the ingredients in cough medicines . This suggests that marketing or some perceived benefit of active ingredients where they are known might influence changes in the pattern of active ingredients over time.…”
Section: Discussionmentioning
confidence: 99%
“…These include the initial introduction and scale up of the Integrated Management of Childhood Illness (IMCI) from 1999, introduction and scale up of Emergency Triage Assessment and Treatment plus admission care (ETAT+) training targeting hospital‐based care from 2006 and efforts at disseminating policy through the media (2009) to discourage prescription of cough mixtures to children . There have, however, been few reports on the use of cough medication in children in the sub‐Saharan region, and most have examined their use in outpatient settings . Three prior studies in Kenyan hospitals using standardised methods and ongoing inpatient surveillance in paediatric wards in 13 Kenyan county hospitals present an opportunity to examine trends in prescription of cough mixtures over the period 2002–2015 in ill children admitted to hospital for whom risks of adverse effects may be higher.…”
Section: Introductionmentioning
confidence: 99%
“…Cough suppressants are more closely related to expectorants, but instead of making mucus easier to expel, they help stop coughing altogether. Side effects associated with this medication are nausea, nervousness, drowsiness, and dizziness [26]. Antihistamines and corticosteroids are most commonly associated with allergies, but they can also be used in wet cough.…”
Section: Discussionmentioning
confidence: 99%
“…Beside the lack of carefulness, a poor understanding of the ingredients in cough medicines was suggested as a cause of the inappropriate dispensing decisions (Kigen G. et al, 2015). A study among hospitalized children across Kenyan hospital between 2002 and 2015 showed that educational, policy mass media interventions and an expansion of the pediatric workforce led to the overall decline in the inappropriate use of cough medicines (Mochuki M. et al, 2016).…”
Section: The Rate Of Appropriate Cmddsmentioning
confidence: 99%